Pre-Partum Feeding and Elimination Behaviour of Kankrej Cows at an Organized Farm (Indian Journal of Animal Production and Management, 2024)
Present study was carried out to assess the effect of parturition on feeding behaviour on before  calving. 21 Kankrej cows were equally grouped into 3 treatments, first parity (T1), second parity (T2)  and 3 or more parity (T3) cows. The behaviour of cows was recorded with two CCTV cameras and  24 hours’ observations were made from recorded video for four days −1, −2, −3 and −7 prior to the  calving. The feeding behaviour was assessed in terms of feeding frequency, feeding duration and  watering frequency. The mean feeding frequency was the highest on the day of calving (30.33±2.07)  followed by day-3 (26.62±1.43), day-2 (25.33±1.46) and Day-7 (24.43±1.40) in a day and the  difference found was significant (P
Keywords: Kankrej cow; parity; feeding behaviour; elimination behaviour; pre-partum behaviour